DEVELOPMENT OF THE LITERARY METHODS IN STRENGTH OF MATERIALS IN HIGHER SCHOOL - Birzul' A. N., Pitilyak D. A. (Current trends in the development of education system, 2023)
the article makes an attempt to generalize the experience of using educational, fiction and memoir literature when lecturing on the course on strength of materials. Specific methodological recommendations are given for using of fiction in certain topics of the strength of materials course. There are creative tasks offered to students and which contain literary subjects.
Keywords: методика преподавания; межпредметные связи; литература; literature; teaching methods; interdisciplinary connections; студенческая наука; сопромат; strength of materials; student science